Stability, Hydrogen Bond Occupancy Analysis and Binding Free Energy Calculation from Flavonol Docked in DAPK1 Active Site Using Molecular Dynamic Simulation Approaches - Adi Tiara Zikri; Harno Dwi Pranowo; Winarto Haryadi (Indonesian Journal of Chemistry, 2021)
Stability and hydrogen bond occupancy analysis of flavonol derivative docked in DAPK1 have been carried out using molecular dynamics simulation approach. Six flavonol derivatives were docked in DAPK1 as protein target, then continued with molecular dynamics simulation. NVT and NPT ensembles were used to equilibrate the system, followed by 20 ns sampling time for each system. Structural stability and hydrogen bond occupancy analyses were carried out at the NVT ensemble, while free binding energy analysis was done at NPT ensemble. From all compounds used in this work, compound B (5,7-dihydroxy-2-(4-hydroxyphenyl)-6-methoxy-4H-chromen-4-one) has a similar interaction with reference ligands (quercetin, kaempferol, and fisetin), and the most stable complex system has the maximum RMSD around 2 Å. Compound C complex has -48.06 kJ/mol binding free energy score, and it was slightly different from quercetin, kaempferol, and fisetin complexes. Even though complex C has similar binding free energy with the reference compound, complex B shows more stable interactions due to their hydrogen bond and occupancy.